THE BRIEF STUDY OF CHINESE CHARACTER ACQUISITION IN ROMANIAN LEARNERS. - Kai CHEN (Studii de Ştiintă şi Cultură)
With the development of Chinese language teaching in Romania, the request for teaching quality in Chinese phonetics and character study is gradually getting more robust. Considering the difference between the Chinese ideographic language and the Romanian phonographic language, Chinese character acquisition presents more challenges than other aspects of Chinese linguistic study. This article attempts to study the current problems in character study by Romanian learners and to put forward suggestions to improve character learning effectiveness, efficiency, and interestingness. The formation of character awareness at the beginning stage of Chinese language study is vital. It can be realized through multimedia, handwriting practice, optimized integrity of character introduction, analysis and practice, and enough exposure to Chinese history and culture behind the character.